1996
DOI: 10.1152/ajpregu.1996.271.5.r1380
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced thermogenesis during recovery from diet-induced weight gain in the rat

Abstract: The present study examined the contribution of energy expenditure to the recovery of body weight after a period of overfeeding. Three groups of 2-mo-old female rats (n = 24) were fed, respectively, a 10% (wt/wt)-fat diet (control), a 35% (wt/wt)-fat diet (high fat) or were force fed 130% of the control diet (tube fed). After 30 days, all groups received the control diet for 18 days of recovery. Both overfeeding protocols significantly increased weight above control levels. This difference disappeared after 7 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 0 publications
4
12
0
Order By: Relevance
“…Previous studies have shown that thyroid hormone levels increase during DIO (1,30). Consistent with these early findings, the current report demonstrates that in DIO rats there is an increase in thyroid hormones as well as an increase in prepro-TRH mRNA, TRH, and pSTAT3 signaling in TRH neurons.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have shown that thyroid hormone levels increase during DIO (1,30). Consistent with these early findings, the current report demonstrates that in DIO rats there is an increase in thyroid hormones as well as an increase in prepro-TRH mRNA, TRH, and pSTAT3 signaling in TRH neurons.…”
Section: Discussionsupporting
confidence: 91%
“…This postoverfeeding sustained elevation of thermogenesis, also observed in laboratory rats [110,111], is consistent with a feedback mechanism existing between thermogenesis and body fat-i.e., the result of an activated adipose-specific control of thermogenesis, which may well have contributed to the subsequent slow return of body weight towards the baseline level after the phase of fat overshooting.…”
Section: Application To a Longitudinal Human Study Of Weight Fluctuatsupporting
confidence: 86%
“…Although no impact of thermal programming could be measured on plasma T3 and T4 levels in our overfed ducks ( Massimino et al, 2019 ), increased expression of this deiodinase in the TM group suggests that embryonic thermal programming may induce a slight TH inactivation in the liver. These data support the hypothesis that embryonic thermal manipulation could have increased the lipid content in the liver by decreasing energy expenditure via thermogenesis ( Almeida et al, 1996 ). Even though we did not measure a difference in surface temperature after the OF period in our programmed ducks, it is not impossible that internal temperature and thus thermogenesis was affected, reducing energy expenditure and thus promoting liver fattening.…”
Section: Discussionsupporting
confidence: 87%
“…Our expression data seem to confirm a global activation of T3 in the liver of overfed ducks, since we measured an increase in THRB and SPOT14 (involved in T3-induced lipid synthesis) expressions, in parallel with a decrease in NCOR (corepressor) and DIO3 (deiodinase responsible for TH inactivation) ( Kinlaw et al, 1995 ; Mendoza and Hollenberg, 2017 ; Sinha et al, 2018 ; Ritter et al, 2020 ). This increase in T3 activity during overfeeding has been proposed as a protective mechanism to limit weight gain by increasing lipid catabolism in favor of energy expenditure through thermogenesis ( Oppenheimer et al, 1991 ; Almeida et al, 1996 ; Silvestri et al, 2005 ). These regulations therefore suggest a protective mechanism for liver cells to limit OF-induced lipid overload, which may alter cell physiology over time.…”
Section: Discussionmentioning
confidence: 99%